Empowering Students: Human Resource Management for Fostering an English Language Environment in Vocational Schools - Marlin, Marlin; Alamsyah, Jaya; Barasa, Larsen; Laksamana, Boy; Permana, Aji (Lembaga Intelektual Muda (LIM) Maluku, 2024)
This study examines the critical dimension of Human Resource Management (HR) in vocational schools, with a particular focus on the active role of students in shaping and maintaining an English-speaking environment. Using a literature review methodology, this study examines empirical evidence and scientific discussions related to students' contributions in shaping the English-speaking environment in vocational education institutions. The results reveal a nuanced perspective on human resources in vocational schools, where students go beyond passive recipients of language instruction, emerging as proactive agents shaping the linguistic landscape. The research covers a wide range of aspects of human resources, including student recruitment, training, motivation, and evaluation, all in the context of their involvement in developing an English-speaking environment. In addition, this study emphasizes the critical role of educators, policymakers, and administrators in facilitating student-driven HR initiatives. It emphasizes the need for a collaborative approach among these stakeholders to effectively empower students in their efforts to achieve English language proficiency. The synthesis of literature emphasizes the importance of creating a supportive and inclusive educational ecosystem that promotes student autonomy and leadership. Paradigm shift in viewing students as dynamic contributors in shaping the English-speaking environment in vocational schools